Discovery Learning - PMRI in Improving Mathematics Literacy of Junior High School Students - Rosita, Anik; Wardono, Wardono; Kartono, Kartono (Universitas Negeri Semarang, 2018)
The lack of mathematical literacy is a worrying thing. It must be noticed that the literacy is an important ability that must be owned by students as future stakeholders. The objective of this study is to analyze the discovery learning - PMRI which effectively improve students' mathematical literacy. The type of research used was quantitative research, experimental research with quasi-experimental design nonrandomized control group, pretest – posttest design. The determination of control and experiment class was by using random sampling technique. The experimental class was treated in the form of discovery learning - PMRI while the control class is given discovery learning - scientific learning. The data were collected using mathematical literacy test, observation, and interview. The data from the data analysis of the final score of mathematical literacy, it is found that (1) the proportion of students in discovery learning-PMRI that fulfills the Minimum Criteria of Mastery Learning is 70, it reaches 70%; (2) the average of students’ mathematical literacy on discovery learning - PMRI is better than the average of students' mathematical literacy on discovery learning, and (3) The improvement of mathematics literacy of discovery learning class - PMRI is higher than discovery learning - scientific class . So it can be concluded that discovery learning – PMRI is effective in improving students' mathematical literacy.